Pemanfaatan Media Berbasis Lingkungan Sebagai Sumber Belajar Pada Pembelajaran Sejarah di SMA Negeri 3 Palu - Priyatna Prasetyawati (Universitas Tadulako, 2021)
The purposes of this study were to describe: (1) the type of environmental media used by the teacher as a learning resource in history learning in senior high school 3 Palu; (2) the use of the environment as a learning resource in history learning in senior high school 3 Palu; and (3) Obstacles or constraints felt by the teacher and students in the use of environment-based media as a source of learning history in history learning. The research design used a qualitative approach. Data were collected using the method of observation, interviews and document analysis. Data were analyzed through data reduction, data classification and presentation, and data verification. The subjects in this study were history teachers, wakasesk curriculum, and students of senior high school 3 Palu. The results showed that: (1) environmentally based media used by history teachers as a learning resource for students was an artificial environment, namely the environment of the Watunonju cultural heritage site. (2) history teachers have utilized environment-based media through outing classes, namely visiting the prehistoric site of Watunonju megaliths as a source of historical learning, by carrying out the planning, implementation and follow-up stages (3) perceived constraints include the large number of students so that teachers are less capable control of individual students, the weather was sometimes not supportive for studying outside the classroom, resulting in inefficient time.